(3LeY GdGSJOdGdGJ hGdJMQjGJ (B/s - (3GdZfGe, WGQb agejs ((3GdLjRI, LeghQjI eUQ GdYQHjI (B:s (3eQcR GdOQGSGJ GdYQHjI ddfTQ hGdJhRjY,s, 2017)
(3jJfGhd cJGH (B((3LeY GdGSJOdGdGJ hGdJMQjGJ(B) (3hGdPj bGe HJCdjag (B((3WGQb agej GdZfGe(B) (3aj MhGdj (B(135) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdJMbjb GdLfGFj hbGfhf GdELQGAGJ GdLfGFjI(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdaUd GdChd (B: (3eQMdI LeY GdGSJOdGdGJ, GdeHMK GdChd (B: (3eGgjI eQMdI LeY GdGSJOdGdGJ, GdeHMK GdKGfj (B: (3OhQ GdedGMXI hGdMS GdCefj aj eQMdI LeY GdGSJOdGdGJ, GdeHMK GdKGdK (B: (3CgOGa eQMdI GdGSJOdGdGJ, GdeHMK GdQGHY (B: (3eSQM GdLQjeI, GdeHMK GdNGeS (B: (3GdTghO, GdeHMK GdSGOS (B: (3GdeQTO GdSQj, GdaUd GdKGfj (B: (3GdJMQjGJ, GdeHMK GdChd (B: (3eGgjI GdJMQjGJ hWHjYJgG hSfOgG, GdeHMK GdKGfj (B: (3GdebUhO HGdLOjI aj GdJMQjGJ, GdeHMK GdKGdK (B: (3eYGjjQ UdGMjI GdJMQjGJ, GdeHMK GdQGHY (B: (3GdGLJgGO ELQGA GdJMQjGJ, GdeHMK GdNGeS (B: (3JUajI GdeYdheGJ, GdeHMK GdSGOS (B: (3eMVQ GdJMQjGJ hGdQbGHI GdbVGFjI, bGFeI GdeQGLY(B.s
(3GdeMJhjGJ (B: (3GdaUd GdChd (B: (3eQMdI LeY GdGSJOdGdGJ, GdeHMK GdChd (B: (3eGgjI eQMdI LeY GdGSJOdGdGJ, GdeHMK GdKGfj (B: (3OhQ GdedGMXI hGdMS GdCefj aj eQMdI LeY GdGSJOdGdGJ, GdeHMK GdKGdK (B: (3CgOGa eQMdI GdGSJOdGdGJ, GdeHMK GdQGHY (B: (3eSQM GdLQjeI, GdeHMK GdNGeS (B: (3GdTghO, GdeHMK GdSGOS (B: (3GdeQTO GdSQj(B-(3GdaUd GdKGfj (B: (3GdJMQjGJ, GdeHMK GdChd (B: (3eGgjI GdJMQjGJ hWHjYJgG hSfOgG, GdeHMK GdKGfj (B: (3GdebUhO HGdLOjI aj GdJMQjGJ (B... (3hehVhYGJ CNQi(B.s
(3HHdjhLQGajI (B: (3UaMI (B131-133.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3GdJMbjb GdLfGFjs; (3bGfhf GdELQGAGJ GdLfGFjIs; (3GdEKHGJ GdLfGFjs; (3LeY GdGSJOdGdGJs; (3GdJMQjGJs; (3eSQM GdLQjeIs; (3GdTghOs; (3GdMS GdCefjs